2022
DOI: 10.1111/ggi.14339
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle as a treatment target for older adults with diabetes mellitus: The importance of a multimodal intervention based on functional category

Abstract: Although the lifespan of people with diabetes has increased in many countries, the age-related increase in comorbidities (sarcopenia, frailty and disabilities) and diabetic complications has become a major issue. Diabetes accelerates the aging of skeletal muscles and blood vessels through mechanisms, such as increased oxidative stress, chronic inflammation, insulin resistance, mitochondrial dysfunction, genetic polymorphism (fat mass and obesity-associated genes) and accumulation of advanced glycation end-prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 147 publications
0
19
0
1
Order By: Relevance
“…The presence of sarcopenia in patients with diabetes may have implications for treatment; for example, resistance-based multicomponent exercise may assist in building muscle mass and, subsequently, increase glucose sensitivity and improve glycemic control. 16 Nonetheless, it should be noted that this study has some limitations that may jeopardize the validity of the pooled analysis. Thus, the results should be carefully interpreted.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The presence of sarcopenia in patients with diabetes may have implications for treatment; for example, resistance-based multicomponent exercise may assist in building muscle mass and, subsequently, increase glucose sensitivity and improve glycemic control. 16 Nonetheless, it should be noted that this study has some limitations that may jeopardize the validity of the pooled analysis. Thus, the results should be carefully interpreted.…”
Section: Discussionmentioning
confidence: 90%
“…The presence of sarcopenia in patients with diabetes may have implications for treatment; for example, resistance‐based multi‐component exercise may assist in building muscle mass and, subsequently, increase glucose sensitivity and improve glycemic control 16 …”
Section: Discussionmentioning
confidence: 99%
“…The effect of DPN on functionality in older adults is commonly seen in geriatric practice. Indeed, previous studies have shown that DPN affects both quality of life and daily functions, not only in the older adults but also in the general population (28,29). A study conducted on older adults found that DPN affects ADLs but not IADLs (8).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the trunk muscle mass significantly increased after 3 months of CR in non-diabetic patients, but not in diabetic patients. The reason why diabetes accelerates the aging of skeletal muscle could involve oxidative stress, chronic inflammation, insulin resistance, mitochondrial dysfunction, and the accumulation of advanced glycation end-products [ 16 ]. If non-diabetic patients were to perform CR for longer in each session and/or increase the number of CR sessions per week, other muscle mass might increase.…”
Section: Discussionmentioning
confidence: 99%